O consumo do medicamento: um estudo das simbologias no discurso publicitário da indústria farmacêutica - Nogueira, Carolina Prieto de Ataliba (2009)
This essay, through discourse analysis, looks for the symbols and values inside the Brazilian pharmaceutical industry s advertising. Its corpus is composed by institutional commercials that promote the medicine in an implicit way, since the actual legislation does not allow the promotion this type of remedy. The study is also composed by an overlook of the consumption society and the function of advertising nowadays; also presenting the market data that marks the strength of the pharmaceutical industry in Brazil. Therefore, this essay is composed by a study of the social space where the discourse is produced and the strategies used in the advertising that promote the use of the medication in a implicit way, analyzing what the product represents, its values